Perception of Japanese singleton and geminate contrasts: A case of Chinese learners with different dialectal backgrounds - Ren, Honghao (Frontiers in Psychology, 2022)
It is widely accepted that the Japanese language is mora-timed, and the geminate obstruent, one of the three special morae in the Japanese language, forms one independent mora. Many studies have shown that perceiving Japanese geminates accurately is especially problematic for learners of Japanese. This study examines the perception of Japanese singleton and geminate contrasts by Chinese learners of Japanese (CLJ) from different dialectal backgrounds and contrasts their perception with Japanese native speakers (JNS). This study conducted two experiments. First, non-synthesized stimuli were used to test each group of participants’ perceptual sensitivity of Japanese singletons and geminates. Second, the categorical perception was accessed by adopting stimuli in which the ratio of constriction duration to entire word duration (CD/EWD) was synthesized from 15% to 60%. Results show that, although learners of Japanese had significantly lower perception levels compared to JNS regardless of their group differences (e.g., L1 background, Japanese language proficiency, etc.), they still experienced some positive transfers of L1 to achieve better perception performance. The results also suggest that CD/EWD can be considered a reliable local cue for both JNS and CLJ in categorizing Japanese singletons and geminates. In addition, the results demonstrate that variables such as medial consonant type and the learner’s Japanese proficiency affect the perception of Japanese singleton and geminate contrasts.